2017
DOI: 10.4172/2167-7921.1000260
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Rat Model of Ankle Osteoarthritis Induced by the Application of Monoiodoacetate

Abstract: Although ankle osteoarthritis is a common human joint disease, the etiological mechanisms underlying the associated pain remain unknown. We developed a new rat model of ankle osteoarthritis (OA) induced by monoiodoacetate (MIA) and evaluated the behavioral and histological characteristics of these animals. 60 male Sprague-Dawley rats were divided into three experimental groups of 20 rats. OA was induced by injecting the metabolic inhibitor MIA (1 mg/30 µl) into the tibiotarsal joint of the right hind paw on tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…In the present study, significant increases in both the right ankle anteroposterior and transverse diameters in the MIA group were noticed at all periods after MIA administration relative to the normal control group. These results are in accordance with previous publications that revealed that MIA injection increased the ankle anteroposterior and transverse diameters [ 22 ]. In the current study, PRP produced a significant decrease in the elevated values of the right ankle anteroposterior and transverse diameters when compared to MIA animals after the 4 th and 3 rd weeks, respectively.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, significant increases in both the right ankle anteroposterior and transverse diameters in the MIA group were noticed at all periods after MIA administration relative to the normal control group. These results are in accordance with previous publications that revealed that MIA injection increased the ankle anteroposterior and transverse diameters [ 22 ]. In the current study, PRP produced a significant decrease in the elevated values of the right ankle anteroposterior and transverse diameters when compared to MIA animals after the 4 th and 3 rd weeks, respectively.…”
Section: Discussionsupporting
confidence: 94%
“…The pannus formation, degeneration of cartilage, synovial hyperplasia, and inflammation exhibited that the MIA-induced osteoarthritis model is closely similar to human OA [ 22 ]. Therefore, in the current work, a rat model of MIA-induced osteoarthritis was established and utilized by ankle intraarticular injection of MIA.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the changes in the transverse and anteroposterior diameters of the normal, diseased, and treated ankles. Ankle diameters were determined by micrometer (Jimbo et al, 2017). The measurements were taken every week (on the zerodays till THE end of experiment) after THE injection of MIA.…”
Section: Ankle Measurementmentioning
confidence: 99%
“…This model may be more evaluable of drug efficiency than other models utilized to evaluate OA medications. It is usually used in rats (Jimbo et al, 2017).…”
Section: Introductionmentioning
confidence: 99%